PENGAPLIKASIAN MEDIA STREAMING PADA M-LEARNING DENGAN MENGGUNAKAN SELULAR CDMA - Santoso, Gatot (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
Telecommunications technology and internet technology represent a most tech-nology liked in the world. In this technological growth enable new breakthrough in learn-ing by mobile use IT peripheral grasp or referred as mobile learning ( m-learning). M-Le-arning have some excess among others ability learn " every where and any where". Exist-ing Problem the peripheral study of m-learning have limitation and many resource of] plat-form so that needed device capable to guarantee compatible between is assorted plat-form. This scheme aim to as learning media which is not limit room and time.